The immunology underlying rheumatic diseases - Al-Mossawi, Hussein (Henry Stewart Talks, 2021)
Classifying immune-mediated rheumatic diseases, Rheumatoid arthritis, The influence of genetics and environmental factors on rheumatic diseases, Ankylosing spondylitis, Key immune pathways involved in the pathogenesis of rheumatic diseases, Evidence for the role of the microbiome in shaping the immune response